Strategi Human Capital Group Department dalam Mengembangkan Keterikatan Karyawan (Employee Engagement) (Studi Kasus: Unit Operasional PT Bumitam - Prihutami, Nurul Dwi; Hubeis, Musa; Puspitawati, Herien (Jurnal Aplikasi Manajemen, 2015)
Employee Engagement is a psychological condition by which can be seen inemotional or intellectual level. Employee Engagement can be seen in their commitment fordoing a better job or from their ability to adapt in the society and persistency to achieve theorganizational goals. This research aimed to identify the internal and external factors whichfocus on human, knowing the level of engagement to the operational unit and also formulatingthe best strategic implemetation aligned with company vision and mission. Questionnairewas used as the methodology and distributed to 529 respondents. Three phases wereused to identify the strategy. Firstly, IFE and EFE matrix in order to analyze the internal andexternal key factors. Second, the key factors were combined with the SWOT matrix. It formulated12 strategic alternatives and then will be map in to 5 strategic categories based onSWOT matrix. After all the phases, QSPM were chosen to produce strategic priority thatcould be applied in the company. As the result, building career path and succession planningare the best options to develop employee engagement and implement in PT BGA's operational.